Wpływ warunków klimatycznych na szerokość przyrostu rocznego jarzębu brekinii (Sorbus torminalis L.) w Wielkopolsce* - Cedro, Anna (Leśne Prace Badawcze, 2016)
The wild service tree ( Sorbus torminalis L.) is a very rare tree species in Poland, which also represents the north-eastern border of its natural range. The majority of this species’ stands is found in Wielkopolska. This study was aimed at examining the relationships between growth and climate for trees of the species Sorbus torminalis L. growing in the Wielkopolski National Park and the forest district Pniewy (Wielkopolska). Samples for the analysis were taken from 63 trees. However, taking into account the missing growth rings and difficult identification of the tree-ring borders in sapwood, only ca. 30% of the samples could be synchronized and dated accurately. Applying classic methods of dendrochronological dating, a 94-year STW chronology was constructed, spanning the years 1920–2013. The chronology, in turn, was used as a basis for dendroclimatological analyses including correlation, response function and pointer years. Climatic data used in the analyses came from the meteorological station in Poznań; providing air temperature and precipitation for a period of 66 years (1948–2013) and 48 years of insolation data (1966–2013). Insolation had the highest negative and precipitation the highest positive impact on the annual growth in May and June. Positive pointer years could be linked to humid months with low insolation during the growth season, while negative pointer years are characterized by deficient precipitation, a large number of sunny hours and high air temperatures in the summer months.